Understanding Islamic Junior High School Students' Attitudes and Thoughts Toward Puberty: A Qualitative Study - Reny Sumino; Pakpahan, Cennikon; Amanda, Bella (Universitas Airlangga, 2023)
Puberty is a transitional period experienced by humans. This period is closely associated with physical, psychological, and emotional changes. Adolescents' responses to puberty can vary. We conducted a qualitative study to determine the definition of puberty and opinions and feelings about facing or experiencing puberty. Our research was conducted in one junior high school by conducting interviews in two focus group discussions. We found two major themes in this study: first is the definition of puberty, and second is the feeling about puberty. Both themes consisted of several sub-themes. The respondents stated that puberty is a maturity period characterized by significant physical, psychological, and emotional changes. The respondents also expressed that they were surprised by the changes they experienced. In addition, for them, puberty is the beginning of new obligations in their social environment. Attraction to the opposite sex makes them more careful and they must be able to control themselves. The need to share friends and role models is one of their recognitions in puberty. Other than that sex education indeed for better information. This study can be used as a reference for understanding the needs of adolescents regarding puberty so that they can better adapt and maintain sexual and reproductive health for good health and well being.